Maslahah in Multi Akad Musyarakah Al Mutanaqishah (MMQ) Based on the Maqasid Syariah System Approach - Siti Hamidah; Fathima Azzahra (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
In response to the growing demand for Sharia-compliant housing financing among the Indonesian population, innovation in financing contracts has become essential. One such innovation, governed by Fatwa Dewan Syariah Nasional, is the Musyarakah Mutanaqishah (MMQ) contract. This study aims to evaluate the potential and challenges faced by MMQ in the context of property financing in Indonesia. By employing the maqasid al-shariah approach, the research examines the maslahah derived from integrating multiple contracts within MMQ and its impact on societal welfare and the growth of the Islamic finance industry. Furthermore, the study addresses Sharia and legal and operational issues that could impede the development of MMQ, offering strategic recommendations to enhance its implementation in practice.